Android application development for dummies - Felker, Donn; Dobbs, Joshua (Hoboken, New Jersey : Wiley Publishing, 2011)
The popularity of the Android market is soaring with no sign of slowing down. The open nature of the Android OS offers programmers the freedom to access the platform's capabilities and this straightforward guide walks you through the steps for creating amazing Android applications
1. The nuts and bolts of android -- 2. Building and publishing your first android application -- 3. Creating a feature-rich applications -- 4. The part of tens
Includes index
Keywords: Application software -- Development